Hidden trap behind the dominance of googling in learning: A study on high school students in Yogyakarta - Grendi Hendrastomo; Muhammad Supraja; Hakimul Ikhwan (SIMULACRA: JURNAL SOSIOLOGI, 2022)
This study seeks to see how students use search engines in learning and uncover the side effects of googling for students during a pandemic. This study combines a phenomenological approach to explore the condition of students while using a search engine and digital ethnography by looking at historical search data. The researcher conducted interviews with high school students in Yogyakarta from various backgrounds and traced the digital footprint of their search accounts. The research results show that googling for students changes learning activities into searching for information. During the pandemic, googling replaces the role of the teacher and becomes a student’s study buddy. Learning becomes an individual activity, “Do It Yourself” becomes a jargon for learning, and the easiest way to learn is to use a search engine. However, googling has hidden dangers that slowly reduce learning abilities, stunting students’ critical thinking. Behind the ease of googling, there are side effects of using search engines that are not realized: (1) Googling eliminates long-term memory, (2) makes students indolent to read in-depth, (3) increases academic dishonesty and (4) reduced critical thinking.